2011
DOI: 10.1016/j.jcma.2011.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Performance of European system for cardiac operative risk evaluation in Veterans General Hospital Kaohsiung cardiac surgery

Abstract: EuroSCORE is simple and easy to use. In the present study, the model demonstrated excellent accuracy in all and various surgical subgroups in VGHKS cardiovascular surgery populations. Good calibration ability in all and different risk categories was identified except for isolated CABG group. Recalibration factors of 0.55 and 0.85 were suggested for the various operative subgroups and risk categories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1
2

Year Published

2012
2012
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
7
1
2
Order By: Relevance
“…'ları (11) 2003 yılında programın logaritmik versiyonunu sundular ve ardından yayınladıkları çalışmalarında lojistik EuroSCORE'un özellikle yüksek risk grubunda mortalite belirlemede standart EuroSCORE'dan daha başarılı olduğunu bildirdiler (14). Takip eden dönemde lojistik EuroSCORE un aditif versiyonun aksine riskli hasta grubunda mortaliteyi yüksek tahmin ettiğini vurgulayan deneyimler yayınlandı (10,15,16). EuroSCORE 2011 yılında yeni çalışmaların öngördüğü üzere güncellenerek EuroSCORE II olarak kullanıma sunuldu.…”
Section: Discussionunclassified
“…'ları (11) 2003 yılında programın logaritmik versiyonunu sundular ve ardından yayınladıkları çalışmalarında lojistik EuroSCORE'un özellikle yüksek risk grubunda mortalite belirlemede standart EuroSCORE'dan daha başarılı olduğunu bildirdiler (14). Takip eden dönemde lojistik EuroSCORE un aditif versiyonun aksine riskli hasta grubunda mortaliteyi yüksek tahmin ettiğini vurgulayan deneyimler yayınlandı (10,15,16). EuroSCORE 2011 yılında yeni çalışmaların öngördüğü üzere güncellenerek EuroSCORE II olarak kullanıma sunuldu.…”
Section: Discussionunclassified
“…However, some clinical research evidence has been published that suggests the original EuroSCORE model now overestimates the operative risk for current adult cardiac surgery as the result of the improvements in surgical techniques and perioperative care over the last few years [4][5][6][7][8][9]. In 2008, we had assessed the performance of the original EuroSCORE model and showed that the original EuroSCORE model gave an imprecise prediction for individual operative risk in patients undergoing heart valve surgery at our centre [10].…”
mentioning
confidence: 99%
“…Recent evidence indicates that EuroSCORE overestimates mortality in MV surgery and the true value is closer to 0.55 × EuroSCORE 51. The MitraClip is considered safe in this high risk patient group even when taking into account the potential recalibration of this score.…”
Section: Discussionmentioning
confidence: 95%